MODERN INTRAOPERATIVE NEUROSONOGRAPHY IN THE CONTEXT OF RADICALITY AND SAFE REMOVAL OF BRAIN TUMORS - S. M Safin; A. B. Gekhtman (Креативная хирургия и онкология, 2017)
The emergence of neuronavigational systems, ultrasonic modules resulted in a new neurosurgery type i.e. cranial image guided surgery, which involves precise verification of borders of the pathological formation, size, regional swelling degree of vascularization of neoplasms and differentiation of feeding arteries and draining veins. The main purpose of this work is to comparatively characterize intraoperative ultrasonography machines capacity of the previous generation B-k medical Falcon 2101 EXL (2003) and Bk medical (2017) 5000 (Denmark) in surgery of brain tumors. The study was conducted on 22 patients with intracranial neoplasms, operated on the basis of the neurosurgical Department of the Republican Clinical Hospital named after G.G. Kuvatov (city of Ufa) The study found that the use of ultrasonic scanner Bk medical 5000 allowed to more accurately visualize the tumor location, which greatly facilitated the task of the surgeon in choosing optimal access to the neoplasm, especially when using convex mini sensor through the trephine opening. Highly detailed normal brain tissue, blood vessels, tumors and zone of regional edema helped determine the optimal operational size, which has reduced the time of surgical manipulation. Using ULTRASONIC module Bk medical5000 inthe mode of intraoperative sonography enables to assess the degree of invasion of the tumor into the lumen of the venous sinus and the nature of collateral blood flow that will determine the level of safe resection of sinus. Using intraoperative ultrasonography after visual removal of diffusely growing tumors there was a good vizualization of residual tumor tissue, which later was removed under ULTRASOUND control Bk medical 5000. Elastography mode in malignant brain tumors enabled to intraoperatively assess the degree of malignancy as well as determine the radicalness of its removal. Implementing into practice the mobile ULTRASOUND module Bk medical 5000 will significantly improve the quality of specialized high-tech patient care in all areas of urgent and selective neurosurgery, reducing the risk of post-operative complications, thereby reducing time limits for patients to stay in hospital.